Effect of Self–Care Educational Program to Improving Quality of Life among Elderly Referred to Health Centers in Zanjan - Fatemeh Salimi; Golamreza Garmaroudi; Seyed Mustafa Hosseini; Azizollah Batebi (Journal of Education and Community Health)
Background and Objectives: Since elderlies are susceptible to various impairments due to different physical and mental problems, they need more attention and abiding and efficient self-care program for their health promotion. The present study investigated the effect of self-care training program on quality of life of elderlies. Materials and Methods: This pre- and post-quasi-experimental study was carried out on 160 elderly clients selected from eight health care centers in Zanjan, Iran. The elderlies were selected by randomized sampling and assigned to two groups of experimental (n = 80) and control (n = 80) groups. The experimental group participated in the self-care training program for six sessions of one hour. The study instruments were questionnaires regarding demographic information and short-form health survey (SF-36). Data analysis was performed using SPSS-22 software by independent t-test, Mann-Whitney and chi-squared. Results: The finding showed a significant difference in mean scores of quality of life between the experimental and control groups after the intervention (P < 0.001). Conclusions: Self-care education to elderlies about the practices of proper nutrition, exercise, rest and medication can prevent several problems and help them to improve their quality of lives.